A Study of International Entrepreneurial Intention Among Entrepreneurs : A TPB Perspective - Singh, Aastha; Sharma, Pooja; Gaba, Parul; Gupta, Shalini (Prabandhan: Indian Journal of Management, 2025)
Purpose : The present paper analyzed the relationship between variables related to international entrepreneurial intention (IEN) among existing entrepreneurs. With the growing importance of business internationalization, the study was conducted to examine the predictors of IEN, with personal norms included as a new variable. Design/Methodology/Approach : Based on the theory of planned behavior (TPB), the study included two independent variables: subjective norms (SN) and personal norms (PN); two mediating variables, attitude toward internationalization (ATI) and perceived behavioral control (PBC); and one dependent variable: IEN. A purposive sampling technique was used for data collection, with entrepreneurs from the Delhi-NCR region serving as respondents. Data were collected through a structured questionnaire with a sample of 300 entrepreneurs, and the hypotheses were tested using Smart PLS SEM 4.0. Findings : The findings showed that the variables ATI and PBC influenced entrepreneurs’ intentions to expand their businesses in the international market, while SN and PN had no significant impact on IEN. In addition, ATI and PBC mediated the relationship between SN and IEN. Practical Implications : To promote and encourage international entrepreneurship among entrepreneurs, policymakers and academics developed strategies to create an international entrepreneurial environment that benefited both entrepreneurs and society at large. This study was not without limitations and provides opportunities for future research. Originality/Value : The research provided socio-economic benefits to society and entrepreneurs by understanding the relationship of the predictors of IEN among entrepreneurs.